2007
DOI: 10.1002/cne.21567
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for pre‐ and postsynaptic localization of Cav1.2 L‐type Ca2+ channels in the rat hippocampus

Abstract: In the hippocampal formation, Ca(v)1.2 (L-type) voltage-gated Ca(2+) channels mediate Ca(2+) signals that can trigger long-term alterations in synaptic efficacy underlying learning and memory. Immunocytochemical studies indicate that Ca(v)1.2 channels are localized mainly in the soma and proximal dendrites of hippocampal pyramidal neurons, but electrophysiological data suggest a broader distribution of these channels. To define the subcellular substrates underlying Ca(v)1.2 Ca(2+) signals, we analyzed the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 76 publications
4
71
0
Order By: Relevance
“…Whereas the expression of NMDARs and L-VGCCs in astrocytes has been debated, our study is in line with previous studies reporting of the presence of these channels in astrocytes (43)(44)(45)(46)(47)(48)50). With respect to astrocyte NMDARs, we find that applying NMDA in the presence of TTX to prevent synaptic transmission directly triggers astrocyte membrane depolarization, and this depolarization is compromised by intracellularly infusing MK-801 or deleting GRIN1 in astrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas the expression of NMDARs and L-VGCCs in astrocytes has been debated, our study is in line with previous studies reporting of the presence of these channels in astrocytes (43)(44)(45)(46)(47)(48)50). With respect to astrocyte NMDARs, we find that applying NMDA in the presence of TTX to prevent synaptic transmission directly triggers astrocyte membrane depolarization, and this depolarization is compromised by intracellularly infusing MK-801 or deleting GRIN1 in astrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Cav1.2 is widely expressed in the heart, pancreas, adrenal gland, and nervous system (Snutch et al, 1991;Dirksen and Beam, 1996). It has been shown that Cav1.2 is located both pre-and postsynaptically in the brain (Tippens et al, 2008) and is present on peripheral nerve axons (Enes et al, 2010). Data from 4-AP-treated samples were first normalized by using the loading (GAPDH) control and then normalized to the control group (without 4-AP).…”
Section: Discussionmentioning
confidence: 99%
“…Although their function is not entirely clear, they may control signal transmission in the axonal arborization. In addition, Cav1.2 (L-type) calcium channels that are sparsely expressed all over hippocampal soma and dendrites are prominently labeled by immunogold electron microscopy in hippocampal axons and in mossy fiber terminals (531).…”
Section: Channels In the Axon Terminalsmentioning
confidence: 99%